IBA57 mutations abrogate iron-sulfur cluster assembly leading to cavitating leukoencephalopathy. (October 2017) - Ishiyama, Akihiko; Sakai, Chika; Matsushima, Yuichi; Noguchi, Satoru; Mitsuhashi, Satomi; Endo, Yukari; Hayashi, Yukiko K.; Saito, Yoshiaki; Nakagawa, Eiji; Komaki, Hirofumi; Sugai, Kenji; Sasaki, Masayuki; et al.
Abstract : Objective: To determine the molecular factors contributing to progressive cavitating leukoencephalopathy (PCL) to help resolve the underlying genotype-phenotype associations in the mitochondrial iron-sulfur cluster (ISC) assembly system. Methods: The subjects were 3 patients from 2 families who showed no inconsistencies in either clinical or brain MRI findings as PCL. We used exome sequencing, immunoblotting, and enzyme activity assays to establish a molecular diagnosis and determine the roles of ISC-associated factors in PCL. Results: We performed genetic analyses on these 3 patients and identified compound heterozygosity for the IBA57 gene, which encodes the mitochondrial iron-sulfur protein assembly factor. Protein expression analysis revealed substantial decreases in IBA57 protein expression in myoblasts and fibroblasts. Immunoblotting revealed substantially reduced expression of SDHB, a subunit of complex II, and lipoic acid synthetase (LIAS). Levels of pyruvate dehydrogenase complex-E2 and α-ketoglutarate dehydrogenase-E2, which use lipoic acid as a cofactor, were also reduced. In activity staining, SDH activity was clearly reduced, but it was ameliorated in mitochondrial fractions from rescued myoblasts. In addition, NFU1 protein expression was also decreased, which is required for the assembly of a subset of iron-sulfur proteins to SDH and LIAS in the mitochondrial ISC assembly system. Conclusions: Defects in IBA57 essentially regulate NFU1 expression, and aberrant NFU1 ultimately affects SDH activity and LIAS expression in the ISC biogenesis pathway. This study provides new insights into the role of the iron-sulfur protein assembly system in disorders related to mitochondrial energy metabolism associated with leukoencephalopathy with cavities.